8q22.1 Microduplication Syndrome: Why the Brain Should Be Spared? A Literature Review and a Case Report - Antonella Gagliano; Erica Pironti; Francesca Cucinotta; Cecilia Galati; Roberta Maggio; Maria Ausilia Alquino; Gabriella Di Rosa (Case Reports in Medicine)
Microduplication of chromosome 8q22.1 is mainly associated to Leri’s pleonosteosis syndrome phenotype, an extremely rare autosomal dominant disease encompassing the GDF6 and SDC2 genes. To date, most of the authors focus their attention only on skeletal symptoms of the disease, and they do not systematically research or describe the co-occurrence of psychiatric illnesses or mental disorders with these muscular-skeletal diseases. In this report, we provide a description of an 8-year-old girl, with a positive family history for both skeletal malformations and bipolar disorders (BD). We suggest a possible association between Leri’s pleonosteosis features and psychiatric symptoms. Furthermore, our report could be added to the large amount of reports that describe the correlation between genetic regions and disease risk for both psychiatric and rheumatological disorders.